Who is the 'smart' resident in the digital age? The varied profiles of users and non-users in the contemporary city. (May 2020) - Hatuka, Tali; Zur, Hadas
This paper is centred on the levels of participation in digital municipal platforms, and its goals are threefold: (1) to assess the normative aspirations and limitations of policy makers and key actors in the municipality with regard to the smart resident idea, with a focus on participation and privacy; (2) to assess and categorise levels of participation in varied social and geographic contexts in the city; and (3) to assess the possible link between participation and privacy practices among users. Empirically, this paper studies the practices of the inhabitants of Tel Aviv-Yafo City, with a focus on the use of digitised services provided by the municipality and the use of the celebrated project 'Digi-Tel' – a digital card that offers to the inhabitants of the city services, discounts, targeted information and benefits around the city. The assessment of the inhabitants' practices is based on a survey that was conducted in four neighbourhoods with different socio-economic, ethnic and geographical characteristics. The survey is supplemented with interviews of prominent figures in the Tel Aviv-Yafo municipality to understand their views on participation and privacy. The paper concludes with a discussion of the varied profiles of the users and non-users of digital platforms in the city, revealing their complex approach to participation in the digital age.